Quantifying black carbon light absorption enhancement with a novel statistical approach - C. Wu; C. Wu; D. Wu; D. Wu; D. Wu; J. Z. Yu; J. Z. Yu; J. Z. Yu (Atmospheric Chemistry and Physics, 2018)
Black carbon (BC) particles in the atmosphere can absorb more light when coated by non-absorbing or weakly absorbing materials during atmospheric aging, due to the lensing effect. In this study, the light absorption enhancement factor, Eabs, was quantified using a 1-year measurement of mass absorption efficiency (MAE) in the Pearl River Delta region (PRD). A new approach for calculating primary MAE (MAEp), the key for Eabs estimation, is demonstrated using the minimum R squared (MRS) method, exploring the inherent source independency between BC and its coating materials. A unique feature of Eabs estimation with the MRS approach is its insensitivity to systematic biases in elemental carbon (EC) and σabs measurements. The annual average Eabs550 is found to be 1.50 ± 0.48 (±1 SD) in the PRD region, exhibiting a clear seasonal pattern with higher values in summer and lower in winter. Elevated Eabs in the summertime is likely associated with aged air masses, predominantly of marine origin, along with long-range transport of biomass-burning-influenced air masses from Southeast Asia. Core–shell Mie simulations along with measured Eabs and absorption Ångström exponent (AAE) constraints suggest that in the PRD, the coating materials are unlikely to be dominated by brown carbon and the coating thickness is higher in the rainy season than in the dry season.